A Successful Management of Ankylosing Spondylitis with Avascular Necrosis Through Ayurveda (International Journal of Ayurveda and Pharma Research, 2023)
This case report aimed to reveal an Ayurvedic approach to a atypical case of Ankylosing Spondylitis with bilateral avascular necrosis of femoral head. Ankylosing Spondylitis (AS) is a condition posing major challenge to health care system.A 29-year-old male subject was diagnosed with ankylosing spondylitis and avascular necrosis of bilateral femur head. By the clinical presentation and thorough Ayurvedic examinations of the subject the case was diagnosed as Gambheera Vatarakta with Asthisoushirya. The case was successfully managed with both Shodhana and Shamana Upacharas according to Ayurveda i.e., for Asthisoushirya, Khara Abhishyandi Snigdha Gunayukta Dravya Prayogam, Asthi Poshakam, Ghrita or Ksheera processed with Tikta Rasa and Vataraktahara Chikitsa, Ama Pachana, Rakta Prasadana, Sneha Virechana and Basti for Gambheera Vatarakta was followed and significant prognosis was achieved.